Peritoneal Dialysis in an Extremely Low Birth Weight Neonate with Ileostomy - Kaul, Amita (Indian J Crit Care Med, 2019)
BACKGROUND: Acute kidney injury (AKI) is a common complication in sick, extremely low birth weight (ELBW) neonates. Peritoneal dialysis (PD) is the treatment modality but is seldom attempted in this patient population. We present a 40-day-old ELBW neonate previously operated for necrotizing enterocolitis with ileostomy who developed AKI. Peritoneal dialysis was started by a modifying intercostal drain. RESULTS: Doing a simple procedure and using a few modifications helped the baby to come out of acute kidney injury. CONCLUSION: Peritoneal dialysis can be technically quite challenging in ELBW neonates but is possible with certain innovative modifications. KEY MESSAGE: Challenging technical problems in potentially fatal conditions sometimes respond to simple innovation. Initiation of early peritoneal dialysis in a sick ELBW with ileostomy and AKI helped saved her life. HOW TO CITE THIS ARTICLE: Kaul A, Jadhav K, Shah S. Peritoneal Dialysis in an Extremely Low Birth Weight Neonate with Ileostomy. Indian J Crit Care Med 2019;23(5):232–233.